Perception of youth in East Malaysia (Sabah) towards the Malaysia national Covid-19 immunisation programme (PICK) - Ramli Dollah; Adi Jafar; Eko Prayitno Joko; Nordin Sakke; Mohammad Tahir Mapa; Colonius Atang; Chong, Vun Hung; Fionna George (Mahidol University, Thailand, 2022)
As a measure to curb the deadly Covid-19 virus, the Malaysian government has implemented the National Covid-19 Immunisation Programme (PICK) in early February 2021 to achieve herd immunity by February 2022. However, several factors have influenced the success of the programme, including accessibility, the role of social media, religious concerns and a variety of other reasons. Therefore, this paper determines the factors that influence the perceptions of the youth in East Malaysia (Sabah) towards PICK. This study uses a self-administered questionnaire through social media applications. A total of 814 respondents consisting of youths in Sabah aged between 18-40 years have been sampled. The raw data have been descriptively analysed (K-Means Clustering, Mean & frequency) and inferentially examined (Mann-Whitney U Test). The respondents’ perceptions are grouped into two clusters: Cluster 1 (54.3%) who exhibited vaccine hesitancy, and Cluster 2 (45.7%), who demonstrated positive perceptions towards the programme. Based on the cluster analysis, this study discovered that most of the respondents in Cluster 1 are inclined to not participate in PICK due to several factors, such as Safety (M=3.25, SD=0.578), Communication (M=3.37, SD=0.441), Psychology (M=3.40, SD=0.568) and Milieu (M=3.32, SD=0.545). The cluster analysis is important to determine different patterns of perceptions of youth in Sabah. This paper argues that if vaccine hesitancy, as indicated in the cluster 1 is not properly addressed, the government’s target to achieve herd immunity will not be successful. Apparently, information issues and management through the mainstream media are extremely important, especially in handling critical matters. As a result, there is a need to revisit the mainstream media's role and determine the causes that contribute to the youths’ rejection of government-sponsored initiatives. The findings will be useful for the government so as to implement the necessary policies, adjustments and improvements to future health regulations or campaigns, especially in addressing issues of misinformation related to health management in the digital era.